Labour beyond Cosatu : mapping the rupture in South Africa's labour landscape - Bezuidenhout, Andries; Tshoaedi, Malehoko (Wits University Press, 2018)
Labour Beyond Cosatu is the fourth volume in the series Taking Democracy Seriously - a ground-breaking, textured and nuanced study on workers and democracy - which was established in the 1990s. The series looks at members of trade unions affiliated to the Congress of South African Trade Unions (Cosatu) and provides a rich database of trade union members and research conducted over the past twenty years. It is one of the very few such resources available to researchers anywhere in the world. Labour Beyond Cosatu paints a complex picture. The 12 chapters of the volume explore various rebellions and conflicts in the trade union sector, starting with the National Union of Mineworkers (NUM) and rivalries between Cosatu affiliates. Unpacking the conflicts between state-sector and private-sector workers, contributors look at the impact of generational and educational shifts, seen by some commentators as proof that Cosatu is now u2018middle classu2019. The book also raises the issue of gender in the unions by usefully locating the controversy around charges levelled at Zwelinzima Vavi in 2013 in the larger context of serious problems in the gender politics within parts of Cosatu. Refuting the image of a union federation solidly committed to the ANC, Labour Beyond Cosatu presents evidence of a sharp decline in support for the ANC within Cosatu, and growing scepticism towards the Alliance. It shows that attempts to understand the labour movement in South Africa in the future will need to include research of smaller, independent unions and social movements. The volumeu2019s contributors make a major contribution to key debates on labour and democracy, providing new material that can potentially shift the discussion in important ways. This book will be of great value to students and researchers in Industrial Sociology, Political Studies, Industrial Psychology and Economics and Management.